IMPLEMENTASI STANDAR NASIONAL PERPUSTAKAAN DI SMA NEGERI DALAM MENINGKATKAN KUALITAS LAYANAN PENDIDIKAN (STUDI PADA PERPUSTAKAAN SEKOLAH SMAN 3 KOTA MALANG) - Lestari Eko Wahyudi; Aulia Puspaning Galih; Rendra Eko Wismanu (Universitas Halu Oleo, 2022)
The National Library Standard is the minimum criteria that used as a reference for the organization, management, and development of libraries. Therefore, every library, both public and school library, must have a service standard to maintain and improve their quality, especially improving the quality of education services for school libraries in SMAN 3 Malang. The research aims to describe and analyze the implementation of national library standards in improving the quality of education services at SMAN 3 Malang. The research method used is a qualitative method approach with observation, interviews and documentation data collection techniques. The data analysis used is developed by Robert K. Yin which includes several stages including: compiling, assembling, reassembling, data interpretation, and conclusion. The conclusion of this study shows that SMAN 3 Malang City has tried to manage the library in accordance with the Regulation of National Library of Indonesia Number 12 of 2017 concerning National Standards for high school Libraries which include: collection standards, facilities and infrastructure standards, service standards, library staff standards, and library management standards, although there are still some standards that have not been met due to inadequate quantity and qualification of library staff and budget constraints. In addition, the location of the school library at SMAN 3 Malang which is less strategic is one of the inhibiting factors in meeting these standards. So, the suggestion that can be formulated in this research is the need for collaboration with various stakeholders (private sector) to be able to access CSR (Corporate Social Responsibility) and universities that have library science study programs for collaborative internships and transfer of knowledge as well as assistance in library management in the SMAN 3 Malang library